Trigeminal neuralgia in an HIV patient - Hashmi Mohammad; Guha Gautam; Saha Bibhuti (Journal of Global Infectious Diseases, 2010)
Trigeminal neuralgia is a painful condition affecting face. Its commonest cause is the tortuous vessels in prepontine cistern. There are other causes also, like brainstem lesions and mass lesions, as well as inflammatory causes. We present a case of an HIV patient with marked involvement of trigeminal nerves, which is a unique finding in immunocompromised patients.